Identification of Turbocharger Noise Sources Taking into Account Design Operating Conditions - Doman, Jozef; Novotný, Pavel; Chmelko, Vladimir (MDPI, 2025)
The paper describes in detail the creation of selected aerodynamic sound sources created by the centrifugal compressor of the turbocharger in operating modes. The description of the creation of aerodynamic sources focuses on the operation of the compressor in a stable area of the characteristic. The analysis is based on a detailed survey of selected aerodynamic sources, mainly vortex shedding, TCN, and buzz-saw phenomena, with a focus on the mechanism of the source and the possibility of identifying the source in the frequency spectrum. Based on the survey, the selected sound sources characterize the assumed frequency ranges at which the sources are estimated to originate. Additional source conditions identified in the survey can be used to develop a methodology for identifying aerodynamic sound sources. In the case of aerodynamic sources of a centrifugal compressor, it was necessary to develop an experimental numerical methodology for their identification with regard to the operating condition of the compressor. The result of the proposed procedure is an algorithm that will enable the identification of aerodynamic sound sources in the frequency spectrum with respect to the operating state of the compressor.
Keywords: turbocharger; centrifugal compressor; aerodynamic noise sources